Blockchain-driven handling of digital freight information: A tensions perspective - T. Gruchmann; Oliver Bischoff (Logistics Research, 2021)
Blockchain technology is provoking significant transformations in the logistics industry, creating a complex environment that challenges business change. This study endeavors to advance the research regarding blockchain-based logistics management by identifying tensions and paradoxes accompanying blockchain adoption for handling digital freight information. Addressing the gap of scarce empirical research on adopting this technology, we conducted 12 expert interviews in the German logistics industry. While confirming and advancing previous research, we found several incompatibilities between the technology and its application, as practitioners tend to adopt blockchain features selectively instead of full acceptance of the respective privacy model. Our analysis reveals that the automation of several functionalities on a platform is among the features of blockchains with the greatest potential to create change in handling digital freight information when related governance mechanisms are in place. Building on these findings, the study proposes main strategies to manage the observed tensions, particularly separation, differentiation, and integration strategies. Thereby, our research contributes to the understanding of digital transformations based on immutability and disintermediation when logistics service providers are engaged in blockchain projects.
Keywords: 650; Blockchain; transport logistics; digital freight information; tensions and paradoxes